Working More? A study of Corporate smart phones’ users - Cavazotte, Flávia de Souza Costa Neves; Lemos, Ana Heloísa da Costa; Brollo, Marcelo da Silva (Organizações & Sociedade, 2014)
The adoption of corporate smart phones to provide employees with mobile access to email is a trend worldwide. In this article, we look at the personal and social implications associated with the use of this technology. To do so, we analyzed the experiences of 42 professionals as they became corporate smart phone users. Although, on the one hand, the use of smart phones is viewed by the participants as promoting relief from email overload and streamlined information exchange, after the device’s adoption they also felt more intensively connected to their work and demands. The technology appears to have allowed considerable extension of work beyond regular business hours and the social context where work traditionally takes place, weakening the boundary between personal and professional life. We discuss how corporate smart phones seem to be insidiously promoting work intensification, highlighting the individual and social implications of the technology.